Расчеты механических свойств β-титановых сплавов из первых принципов - Каспарян, Сергей Олегович (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The mechanical properties of Ti-X alloys (X = V, Nb) with BCC structure were calculated by the exact muffin-tin orbital method within the density functional theory. It is shown that the elastic moduli C11 and C12 are increased but C44 is decreased with an increased V or Nb content in the β-Ti based alloy. Undoped β-Ti and alloy doped with V and Nb up to 3–4 at. % is found to be mechanical unstable due to negative value of C'. The obtained results are in good agreement with experimental data.